2012
DOI: 10.7326/0003-4819-156-7-201204030-00411
|View full text |Cite
|
Sign up to set email alerts
|

Antivirals for Treatment of Influenza

Abstract: Therapy with oral oseltamivir and inhaled zanamivir may provide a net benefit over no treatment of influenza. However, as with the randomized trials, the confidence in the estimates of the effects for decision making is low to very low. PRIMARY FUNDING SOURCES: World Health Organization and McMaster University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
82
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(93 citation statements)
references
References 79 publications
8
82
3
Order By: Relevance
“…Our findings that early initiation of NAI treatment (≤48 hours after illness onset) compared with later was associated with a significant reduction in IRP and ‘any pneumonia’ corroborate those previously reported from observational data on hospitalised influenza patients 9, 17, 19. These trends were consistently observed across multiple subgroups: laboratory‐confirmed influenza, adults, children, pregnant women and adults requiring critical care (but not children).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings that early initiation of NAI treatment (≤48 hours after illness onset) compared with later was associated with a significant reduction in IRP and ‘any pneumonia’ corroborate those previously reported from observational data on hospitalised influenza patients 9, 17, 19. These trends were consistently observed across multiple subgroups: laboratory‐confirmed influenza, adults, children, pregnant women and adults requiring critical care (but not children).…”
Section: Discussionsupporting
confidence: 90%
“…Neuraminidase inhibitors (NAIs), primarily oseltamivir and zanamivir, were widely recommended for patients with suspected or confirmed influenza A(H1N1)pdm09 virus infection 6, 7. However, prior to the 2009–2010 pandemic, evidence of their effectiveness in seasonal influenza, while strong for modest symptom alleviation, was less robust for reductions in pneumonia incidence or improvements in pneumonia outcome 8, 9, 10. The findings from meta‐analyses have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudden death is another concern [5-7]. A causal association between oseltamivir use and abnormal behaviours or sudden death has not been established and it is considered negative [1,2] based on retrospective observational studies [8-12], systematic reviews of retrospective observational studies [13,14] and a systematic review and meta-analysis of randomized controlled trials of oseltamivir treatment for influenza of adults [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Various observational studies have provided evidence of improved survival with prompt antiviral treatment within 48 hours of influenza symptom onset, however not all studies have found this clear benefit 8, 9, 10, 11. The purpose of this ecological analysis was, therefore, to examine the relationship of mortality specific to pandemic H1N1 influenza and NAI supply at the level of WHO Member States and provide further evidence of the aggregate role that NAIs may play in reducing influenza mortality in future pandemics.…”
Section: Introductionmentioning
confidence: 99%